2020
DOI: 10.3233/ch-209003
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhanced ultrasonography (CEUS) to detect abdominal microcirculatory disorders in severe cases of COVID-19 infection: First experience

Abstract: U n c o r r e c t e d A u t h o r P r o o fClinical Hemorheology and Microcirculation xx (20xx) x-xx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 16 publications
2
60
0
3
Order By: Relevance
“…In preliminary studies, the potential of CEUS for a dynamic recording of organ microperfusion in severe COVID-19 infection could be demonstrated with regard to abdominal sonography [21]. However, this raises the question of accompanying changes in the CEUS dynamics from the basal lung sections near the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies, the potential of CEUS for a dynamic recording of organ microperfusion in severe COVID-19 infection could be demonstrated with regard to abdominal sonography [21]. However, this raises the question of accompanying changes in the CEUS dynamics from the basal lung sections near the diaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Possible indications for the use of CEUS would be an increasing compression of basal lung sections with constriction of arterial vessels, restriction of arterial capillary microcirculation and restriction of respiratory function. In addition, CEUS also enables the dynamic assessment of organ microcirculation, especially of the liver and kidneys [21]. Here, reduced perfusion is common in severe infectious to septic clinical pictures and, as with COVID-19 patients, may require the use of ECMO treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the CS or the direct virus attack might provoke a microcirculatory dysfunction in COVID-19 patients it is not yet understood. To date, there are few studies of microvascular function in COVID-19 [12]. But, many previous studies have reported that CS can provoke massive microvascular dysfunction in critical ICU patients suffering from similar disease [13].…”
Section: R Martini / the Compelling Arguments For The Need Of Microvmentioning
confidence: 99%
“…Progress. A preliminary report of 5 patients indicates the potential of CEUS in assessing the microcirculation of the abdominal viscera in severely impaired patients showing reduced arterial perfusion, uneven contrast distribution and areas with microinfarcts [16].…”
mentioning
confidence: 99%